Functional Anatomy of the Spine - Middleditch Alison; Oliver Jean (Elsevier - Butterworth Heinemann, 1991)
This book provides the reader with vital background information on normal function and abnormal disfuction of the spine, the response of tissues to injury and the effects of age related changes. Foreword, Preface, Structure of the Vertebral Column, Intervertebral Discs, Muscles of the Vertebral Column, Blood Supply of the Spinal Cord and the Vertebral Column, Normal Movement, Sacroiliac Joints, Innervation of the Vertebral Column, Biomechanics of the Spinal Cord and Meninges, Embryology and Development and Ageing and Degeneration, Posture, Index.